EXPORT ACTIVITIES OF UKRAINIAN ENTERPRISES IN THE SYSTEM OF ECONOMIC SECURITY: AN ANALYTICAL DIMENSION - Nebis, Vitalii (Current Problems of Sustainable Development, 2026)
The article examines the role of export activities of Ukrainian enterprises within the system of national economic security under conditions of wartime instability, geopolitical turbulence, and macroeconomic challenges. It is substantiated that export activity serves not only as a source of foreign exchange earnings but also as a strategic factor in ensuring macroeconomic stability, preserving production capacity, supporting financial resilience, and integrating Ukraine into the European economic space. The study analyzes the impact of export activity on the key components of economic security, including foreign economic, production, macroeconomic, financial, and investment-innovation security. Particular attention is devoted to the analytical dimension of export management in the context of increasing uncertainty and transformation of international trade relations. The research identifies that the effectiveness of export-oriented enterprises increasingly depends on the quality of accounting and analytical support, access to reliable information resources, risk monitoring mechanisms, and the ability to adapt to regulatory requirements of the EU markets. The dynamics of Ukraine’s export of services during 2022–2024 are analyzed, revealing a gradual recovery of external economic activity after the significant decline caused by the full-scale war. The study confirms the growing share of EU countries in the structure of Ukrainian service exports, indicating the strengthening of European integration processes and the reorientation of foreign trade flows toward EU markets. The paper also identifies the dominant sectors in the export structure of services, particularly telecommunications, computer and information services, transport services, and processing services, which demonstrate the increasing role of the digital economy and logistics infrastructure in ensuring external economic resilience. Furthermore, the article systematizes the key sources of analytical support for export management at the mega-, macro-, meso-, and microeconomic levels. The necessity of developing risk-oriented approaches to accounting, internal control, and internal audit of export operations is substantiated. It is concluded that high-quality analytical support and integrated monitoring of financial, logistical, institutional, and ESG-related risks are critical prerequisites for strengthening the competitiveness and sustainability of Ukrainian enterprises in international markets.
Keywords: economic security; regulatory framework; reporting; accounting; analysis; sustainability